Low-temperature chemical vapor deposition of cobalt oxide thin films from a dicobaltatetrahedrane precursor. Issue 79 (27th October 2017) - Melzer, Marcel; Nichenametla, Charan K.; Georgi, Colin; Lang, Heinrich; Schulz, Stefan E.
Abstract : Application of a novel liquid cobalt precursor, which forms cobalt oxide films at low temperatures using relatively simple CVD process. Abstract : Cobalt oxides are a promising anode material for lightweight rechargeable lithium-ion batteries. Thus, the low temperature deposition of cobalt oxide is a key-technology for the production of flexible energy storage systems enabling novel application opportunities such as wearables. To satisfy the emerging process requirements the dicobaltatetrahedrane precursor [Co2 (CO)6 ( η 2 -H–CC– n C5 H11 )] was investigated for the low-temperature chemical vapor deposition of cobalt oxides. Oxygen, water vapor and a combination of both were examined as possible co-reactants. In particular, wet oxygen proves to be an appropriate oxidizing agent providing dense and high purity cobalt oxide films within the examined temperature range from 130 °C to 250 °C. Film growth occurred at temperatures as low as 100 °C making this process suitable for the coating of temperature-sensitive and flexible substrates.